2017
DOI: 10.1111/jgh.13638
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of the highly effective direct‐acting antivirals in the treatment of chronic hepatitis C in Hong Kong

Abstract: The most desirable costs of the Highly Effective DAAs would be below US$43,553 if Sofosbuvir-PR rescue therapy is used and below US$56,985 if Boceprevir-PR therapy is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The high list price of DAA treatment prohibits the Hong Kong government to set it as the first‐line treatment for HCV due to limitations in fixed healthcare budgets. Yet our previous cost‐effectiveness analysis showed that even with the current local price ranging from US$30 000–$50 000 for a 12‐week course . This ineffective reimbursement policy in Hong Kong was the main reason leading to such a low treatment uptake and low SVR rates.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The high list price of DAA treatment prohibits the Hong Kong government to set it as the first‐line treatment for HCV due to limitations in fixed healthcare budgets. Yet our previous cost‐effectiveness analysis showed that even with the current local price ranging from US$30 000–$50 000 for a 12‐week course . This ineffective reimbursement policy in Hong Kong was the main reason leading to such a low treatment uptake and low SVR rates.…”
Section: Discussionmentioning
confidence: 95%
“…Yet our previous cost-effectiveness analysis showed that even with the current local price ranging from US$30 000-$50 000 for a 12-week course. 24 This ineffective reimbursement policy in Hong Kong was the main reason leading to such a low treatment uptake and low SVR rates. As the treatment uptake of PegIFN/RBV was not high and treatment is not effective in more than 60% of patients, retreatment with DAA would be required in 40% of PegIFN/RBV-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these studies do not target the HIV positive MSM population, and consequently do not have any implication on micro-elimination strategies. Thirdly, the cost-effectiveness studies conducted in other Asian countries are from Hong Kong, 17 , 18 Japan, 19 and Singapore, 20 which are high-income countries and therefore not comparable to Thailand. Among other comparable low- and middle-income resource settings, China 21 did not find it cost-effective to use DAAs; a study conducted in Vietnam 22 found DAAs cost-effective but took interferon-based treatments as a comparison, while another study in India 23 uses no DAAs as a comparison scenario while concluding that they are cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous model of GT1infected CHC patients using a decision tree structure, SOF, LDV/SOF, and OMB/PAR/RIT + DAS were all cost-effective compared to PegIFN + RBV, regardless of treatment history and presence of cirrhosis, with ICURs less than US$30,000 per additional cure [62]. In addition, hypothetical highly effective DAAs (defined as having an SVR of 100%) were projected to be the most cost-effective compared to PegIFN + RBV at a price of up to US$43,553 in countries where SOF + PegIFN + RBV is the standard of practice and up to US$56,985 where boceprevir + PegIFN + RBV is the standard [56]. Actual costs of DAAs in Hong Kong (Table 3) are lower than these estimates, further supporting the agents' cost-effectiveness versus PegIFN + RBV.…”
Section: Discussionmentioning
confidence: 99%